Regenerative Medicine Using Non-Fetal Sources of Stem Cells - Bhattacharya, Niranjan; Stubblefield, Phillip George (Springer London : Imprint: Springer, 2015)
This book represents a major contribution to the emerging science of regenerative medicine using non-fetal sources of stem cells. The Editors, Dr Niranjan Bhattacharya and Professor Phillip Stubblefield, have brought together some of the most pre-eminent scientists working on regenerative medicine to share information on currently ongoing work in this area alongside unpublished observations that will help to shape the contours of future therapies. Regenerative Medicine: Using Non-Fetal Sources of Stem Cells discusses the potential clinical and therapeutic applications using non-fetal stem cells as well as providing instruction on the collection, isolation and characterization of stem cells from various non-fetal sources, such as menstrual blood, adipose tissue, breast milk and uprooted decidual teeth. This book will be an invaluable resource for both active researchers and those entering the field. The Editors truly hope that the text will act as a stimulant to professionals and clinical scientists, who may be inspired to further the work of the pioneering scientists who have contributed to this volume.